2002
DOI: 10.1128/jvi.76.6.2835-2847.2002
|View full text |Cite
|
Sign up to set email alerts
|

Purification and Characterization of Oligomeric Envelope Glycoprotein from a Primary R5 Subtype B Human Immunodeficiency Virus

Abstract: Human immunodeficiency virus (HIV) continues to be a major public health problem throughout the world, with high levels of mortality and morbidity associated with AIDS. Considerable efforts to develop an effective vaccine for HIV have been directed towards the generation of cellular, humoral, and mucosal immune responses. A major emphasis of our work has been toward the evaluation of oligomeric (o-gp140) forms of the HIV type 1 (HIV-1) envelope protein for their ability to induce neutralizing antibody response… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
101
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 98 publications
(108 citation statements)
references
References 125 publications
7
101
0
Order By: Relevance
“…We hypothesize that the gp140 and gp160 DNA vaccines presented native Env conformations in vivo that were boosted poorly or not at all by these adjuvanted, and probably at least partially denatured, gp120 monomer proteins. Although native gp120 can bind conformation-dependent broad neutralizing antibodies (61), elicit neutralizing antibodies (26), and boost DNA priming (3), there is evidence that oligomeric envelope proteins are more effective in boosting broader responses against primary HIV-1 isolates (14,60).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We hypothesize that the gp140 and gp160 DNA vaccines presented native Env conformations in vivo that were boosted poorly or not at all by these adjuvanted, and probably at least partially denatured, gp120 monomer proteins. Although native gp120 can bind conformation-dependent broad neutralizing antibodies (61), elicit neutralizing antibodies (26), and boost DNA priming (3), there is evidence that oligomeric envelope proteins are more effective in boosting broader responses against primary HIV-1 isolates (14,60).…”
Section: Discussionmentioning
confidence: 99%
“…Production of gp120 was monitored by enzyme-linked immunosorbent assay (ELISA) at all stages of production, and purity was verified by SDS-PAGE. The SF162 protein was prepared as previously described (60).…”
Section: Methodsmentioning
confidence: 99%
“…158 Recently, we reported the purification and characterization of stable trimeric Env protein from US4 (Subtype B R5 isolates). 159 We also purified and characterized trimeric protein from SF162 and demonstrated that it elicited strong antibody responses in rabbits which neutralized two out of six heterologous subtype B primary isolates. 168 To further enhance the immunogenicity of trimeric Env, we have introduced a partial deletion of the V2 loop and expressed, purified and characterized this novel Env immunogen.…”
Section: Structural Optimization To Target Conserved Neutralization Ementioning
confidence: 99%
“…Several approaches have been tried with reasonable success. 88,[155][156][157][158][159][160][161][162][163][164][165][166] Yang and colleagues used GCN4-stabilized oligomers to demonstrate that antibodies induced by oligomeric gp140 were more effective at neutralizing heterologous primary isolates, compared to antibodies elicited by the corresponding monomeric gp120 protein. 167 Earl and colleagues made similar observations in rhesus macaques using a trimeric Env protein from SIV.…”
Section: Structural Optimization To Target Conserved Neutralization Ementioning
confidence: 99%
“…SF162 envelope glycoproteins were purified as described previously (6,7). Note that all the experiments carried out with the socalled gp140 in this study were in fact done with the V2 deleted version of gp140 (gp140⌬V2SF162).…”
Section: Methodsmentioning
confidence: 99%